A research on low-earth-orbit signal-of-opportunity interference suppression algorithm based on adaptive signal iterative subspace projection technique - Yao, Lihao; Fan, Bin; Qin, Honglei; Xian, Deyong; Gu, Boyun; Sha, Hai; Guan, Gangqiang; Liu, Zhijun; He, Donghan; Zhang, Liwei (Frontiers in Physics, 2025)
Signal-of-Opportunity (SOP) positioning based on Low-Earth-Orbit (LEO) constellations has gradually become a research hotspot. LEO satellite SOP positioning possess strong anti-jamming capabilities due to their large quantity, wide spectral coverage, and high signal power. However, few studies have deeply investigated their anti-jamming performance, particularly regarding the most common interference type faced by ground receivers - Periodic Frequency Modulation (PFM) interference. The downlink signals of LEO satellites differ significantly from those of Global Navigation Satellite Systems (GNSS) based on Medium-Earth-Orbit (MEO) or Geostationary-Earth-Orbit (GEO) satellites, making traditional interference suppression methods inapplicable. In this paper, we utilize the generalized periodicity of PFM interference signals and the characteristics of LEO constellation signals to propose an Adaptive Signal Iterative Projection and Interference Suppression (ASIPIS) algorithm. This algorithm concentrates the energy of PFM interference, which is dispersed over a wide bandwidth, into a few frequency points, enhancing the concentration of the interference and its separation from the LEO satellite signals. This effectively reduces the overlap between LEO satellite signals and interference. The algorithm then uses subspace projection to map the interference and the desired signal into different subspaces, eliminating the interference components and thus reducing the damage to the desired signal during the interference suppression process. Simulations and experiments demonstrate that compared to conventional methods, ASIPIS effectively eliminates single/multi-component PFM interference, improves suppression performance under narrow-bandwidth/high-power conditions, and overcomes limitations of traditional PFM interference suppression approaches for single-antenna LEO signal reception. The significant performance improvement in LEO anti-jamming scenarios against PFM interference confirms the algorithm's value.